Monitoring Shifts in the Conformation Equilibrium of the Membrane Protein Cytochrome P450 Reductase (POR) in Nanodiscs - Wadsäter, Maria (American Society for Biochemistry and Molecular Biology, 2012)

(untitled)
Nanodiscs are self-assembled ∼50-nm(2) patches of lipid bilayers stabilized by amphipathic belt proteins. We demonstrate that a well ordered dense film of nanodiscs serves for non-destructive, label-free studies of isolated membrane proteins in a native like environment using neutron reflectometry (NR). This method exceeds studies of membrane proteins in vesicle or supported lipid bilayer because membrane proteins can be selectively adsorbed with controlled orientation. As a proof of concept, the mechanism of action of the membrane-anchored cytochrome P450 reductase (POR) is studied here. This enzyme is responsible for catalyzing the transfer of electrons from NADPH to cytochrome P450s and thus is a key enzyme in the biosynthesis of numerous primary and secondary metabolites in plants. Neutron reflectometry shows a coexistence of two different POR conformations, a compact and an extended form with a thickness of 44 and 79 Å, respectively. Upon complete reduction by NADPH, the conformational equilibrium shifts toward the compact form protecting the reduced FMN cofactor from engaging in unspecific electron transfer reaction.